1993
DOI: 10.1083/jcb.122.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-dependent variations in the subcellular distribution of alpha-mannosidase I and II

Abstract: Abstract. a-mannosidases I and II (Man I and 11) are resident enzymes of the Golgi complex involved in oligosaccharide processing during N-linked glycoprotein biosynthesis that are widely considered to be markers of the cis-and medial-Golgi compartments, respectively. We have investigated the distribution of these enzymes in several cell types by immunofluorescence and immunoelectron microscopy. Man 1I was most commonly found in medial-and/or trans-cisternae but showed cell type-dependent variations in intra-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
202
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(223 citation statements)
references
References 59 publications
21
202
0
Order By: Relevance
“…Comparison of the fluorescence of HDQ83 protein aggregates with the immunostaining of ␥-tubulin, a known marker for the centrosome (Dictenberg et al, 1998), revealed that both structures colocalize at least partially (Figure 2d). On the other hand, the fluorescence of the HD exon 1 protein aggregates did not overlap with the immunostaining of ␣-mannosidase II, a marker for the Golgi apparatus (Figure 2e), indicating that the Golgi apparatus, which is also located in the perinuclear region (Velasco et al, 1993), is distinct from the HDQ83 protein aggregates. Accumulation of mutant HDQ83 protein in 293 Tet-Off cells also appeared to cause the reorganization of the intermediate filament vimentin.…”
Section: Cytoplasmic Hd Exon 1 Protein Aggregatesmentioning
confidence: 93%
“…Comparison of the fluorescence of HDQ83 protein aggregates with the immunostaining of ␥-tubulin, a known marker for the centrosome (Dictenberg et al, 1998), revealed that both structures colocalize at least partially (Figure 2d). On the other hand, the fluorescence of the HD exon 1 protein aggregates did not overlap with the immunostaining of ␣-mannosidase II, a marker for the Golgi apparatus (Figure 2e), indicating that the Golgi apparatus, which is also located in the perinuclear region (Velasco et al, 1993), is distinct from the HDQ83 protein aggregates. Accumulation of mutant HDQ83 protein in 293 Tet-Off cells also appeared to cause the reorganization of the intermediate filament vimentin.…”
Section: Cytoplasmic Hd Exon 1 Protein Aggregatesmentioning
confidence: 93%
“…Although not resolved as clearly as in chemically fixed specimens, the organelles retained part of their dense appearance and were therefore easily recognized. The polyclonal antibodies used were addressed to components of two of the investigated organelles, the Ca2+ binding protein calreticulin (CRT), specific of the ER lumen (Villa et al, 1993;Nash et al, 1994), and mannosidase II (MA-NII), a GC membrane enzyme (Velasco et al, 1993). With the first, the immunogold labeling was strong, uniformly and strictly confined to the lumen of ER cisternae ( Figure 2A) including the nuclear envelope ; short and often slightly swollen ER cisternae, most often covered with discrete, dense polysomes; a clearly visible GC and various dense granules (arrows).…”
Section: Resultsmentioning
confidence: 99%
“…The underlying organization of these subcompartments is not fully known, but it must be maintained in the face of continuous bidirectional traffic. Although it is clear that resident proteins are localized to discrete compartments in the organelle (Dunphy and Rothman, 1985), their distribution may substantially overlap (Nilsson et al, 1993;Velasco et al, 1993). Also, the subcompartment localization of some Golgi-associated proteins varies with cell type (Brown and Farquhar, 1987;Colley, 1997).…”
Section: Introductionmentioning
confidence: 99%